High-strength cadmium-free low-silver silver solder

By adopting specific ratios and processes in low-silver brazing materials, high-strength cadmium-free low-silver brazing materials are prepared, which solves the problem of excessive temperature of existing brazing materials, achieves lower melting temperature and higher brazing joint strength, and meets the brazing needs of copper and copper alloy structures.

CN119658211AActive Publication Date: 2025-03-21NANJING UNIV OF SCI & TECH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411715455.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-21
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing low-silver brazing materials have high temperatures in solid and liquid phase lines, which leads to the copper and copper alloy structures being easily "overfired" and "softened" during the brazing process, affecting the brazing quality.

Method used

The high-strength, cadmium-free and low-silver brazing material was prepared by the intermediate frequency smelting process and the method of coating nano powders with copper foils, high-strength, cadmium-free and low-silver brazing material was prepared by the intermediate frequency smelting process and the method of coating nano powders with copper foil.

Benefits of technology

The solid and liquid phase line temperature of the solder material is significantly reduced, reaching solid phase line ≤660℃ and liquid phase line ≤720℃, and the brazing seam strength and processing performance of the solder material are improved, meeting the brazing needs of copper and copper alloy structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156784530000061
    Figure BDA0005156784530000061
Patent Text Reader

Abstract

The invention discloses a high-strength cadmium-free low-silver silver solder. The silver brazing filler metal is prepared from the following components in percentage by mass: 7.5 percent to 8.5 percent of Ag, 38.5 percent to 43.5 percent of Zn, 14.5 percent to 15.5 percent of Sn, 5.0 percent to 5.5 percent of Ni, 0.0005 percent to 0.001 percent of nano NbBe12, 0.0005 percent to 0.001 percent of nano MoBe12 and the balance of Cu. The solidus temperature of the silver brazing filler metal is smaller than or equal to 660 DEG C, the liquidus temperature of the silver brazing filler metal is smaller than or equal to 720 DEG C, and when the silver brazing filler metal is matched with commercially available FB102 brazing flux for brazing red copper-Q235 steel, red copper-brass and brass-stainless steel, the shear strength of a brazed joint is remarkably higher than that of a brazed joint of existing BAg12CuZn (Si) brazing filler metal and BAg5CuZn (Si) brazing filler metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brazing materials of metal materials, and relates to a high-strength cadmium-free and low-silver silver brazing filler metal. Background Art

[0002] With the increase in the use of silver solder, in order to reduce material costs, the demand for low-silver silver solder is increasing, especially for low-silver silver solder with a silver content of less than 20% and high strength and a low solid-liquid phase temperature (such as a melting temperature range of 680℃~745℃ to meet the brazing of copper and copper alloy structures), which has always been an urgently needed product in the market. Existing literature such as the BAg20CuZn(Si) solder recommended in GB / T10046-2018 "Silver Solder" has a melting temperature range of 690℃ solidus, but the liquidus of 810℃ is too high to meet the requirements; the BAg5CuZn(Si) solder with a low silver content in GB / T 10046-2018 "Silver Solder" has a melting temperature range of 820℃ solidus and 870℃ liquidus; the melting temperature range of BAg12CuZn(Si) solder is 800℃ solidus and 830℃ liquidus. The above two low-silver solders provide users with a cost-reducing option. However, the solidus and liquidus temperatures of the solders are both higher than 800°C, which can easily cause "overburning" and "softening" of copper and copper alloys (e.g., the melting point of H58 brass is about 934-967°C), which is not conducive to the brazing of copper and copper alloy structures. Therefore, the development of cadmium-free low-silver solders with lower silver content and better solder performance has always been a hot topic faced by technicians in the relevant manufacturing industry.

[0003] The inventors found through literature search that in the published Chinese patent documents, the technical information about the new low-silver solder is briefly listed. For example, document CN 116871736A reports a cadmium-free low-silver solder and a preparation method thereof. The cadmium-free low-silver solder is composed of 4.0% to 5.0% Ag, 40.0% to 45.0% Zn, 11.0% to 13.0% Sn, 0.5% to 1.5% In, 0.5% to 1.5% Ga, 0.5% to 1.5% Ni, 0.01% to 0.05% nano CeO2, 0.01% to 0.05% nano Y2O3, and the balance is Cu. The solder of the invention has a solidus temperature of ≤735°C and a liquidus temperature of ≤780°C; document CN 115533365A reports a cadmium-free low-silver solder, characterized by: 8.0% to 10.0% Ag, 38.0% to 42.0% Zn, 6.0% to 10.0% Sn, 1.5% to 2.5% In, 1.5% to 2.5% Ga, 1.5% to 2.5% Ni, 0.0001% to 0.0005% nano HfC, 0.0001% to 0.0005% nano ZrC, and the balance is Cu. The solder solidus temperature of the invention is ≤700°C, and the liquidus temperature is ≤750°C. The Ag content of the above two low-silver solders is less than or equal to 10%, but both are added with relatively high content of In and Ga elements, and the cost is still high. A large number of studies have pointed out that the common feature of reducing the melting temperature (such as solidus temperature and liquidus temperature) of cadmium-free silver solder is to add at least one or more low-melting-point elements such as Sn (melting point 231.9℃), In (melting point 156.6℃), Ga (melting point 29.76℃), Li (melting point 180.5℃) and alloying elements Ni that can reduce the melting point of solder. Since In, Ga and Li are "rare elements", the annual production in the world is also very limited. The price of In and Ga is equivalent to or higher than that of silver. It can be seen that adding In and Ga elements to reduce the melting temperature of silver solder is not the best choice. Due to the rapid development of new energy vehicles, the price of Li has skyrocketed to 3 million yuan / ton (3,000 yuan / kg) in recent years, which is much higher than Cu (about 80 yuan / kg). Therefore, the addition of Li element also greatly reduces the value of mass production application; the price of Sn element is not high compared to Ag and its reserves are relatively abundant. However, when Sn is added in large quantities, it is easy to form hard and brittle intermetallic compound Cu6Sn5, which makes silver solder "difficult to process", so the amount of Sn added is generally difficult to exceed 10%.According to the document GB / T 10046-2018 "Silver Solder", the known high-tin solders, except for BAg60CuSn solder, in which the Sn addition amount can reach 9.5% to 10.5%, the general addition amount in the Ag-Cu-Zn-Sn series solders is 1.5% to 2.5%. Only in some individual models such as BAg56CuZnSn, the Sn addition amount is 4.5% to 5.5%.

[0004] Although document CN 115533365A reports that the Sn addition amount can be as high as 10.0%, and the solidus temperature of the obtained cadmium-free low-silver solder is ≤700°C, and the liquidus temperature is ≤750°C; document CN 116871736A reports that the Sn addition amount can be as high as 11.0%~13.0%, and its solidus temperature is ≤735°C, and its liquidus temperature is ≤780°C, which is close to or even better than the melting temperature of BAg20CuZn(Si) solder, and can basically meet the brazing requirements of copper and copper alloy structures.

[0005] However, since the above-mentioned cadmium-free and low-silver solders all contain high levels of In and Ga, in addition to the high cost factor, In and Ga are "rare metals" and are not suitable for large-scale use, both in terms of their reserves on the earth and their annual production worldwide. Therefore, how to use the abundant Sn element to replace In and Ga, and add In and Ga elements as "trace elements" to achieve the purpose of lowering the melting temperature of the new solder and improving the solder joint strength, further research and discussion is needed. Summary of the invention

[0006] The invention aims to provide a high-strength cadmium-free and low-silver silver solder, wherein the Ag content of the silver solder is in the range of 7.5% to 8.5%, the liquidus temperature is ≤750°C, and the solder is suitable for brazing materials such as copper-H58 brass, copper-Q235 steel, and brass-304 stainless steel, thereby meeting the needs of solder users to reduce costs, improve product quality, and enhance product market competitiveness.

[0007] The technical solution for achieving the purpose of the present invention is as follows:

[0008] A high-strength cadmium-free low-silver silver solder, which is composed of 7.5% to 8.5% Ag, 38.5% to 43.5% Zn, 14.5% to 15.5% Sn, 5.0% to 5.5% Ni, and 0.0005% to 0.001% nano NbBe in proportion by mass percentage. 12 , 0.0005%~0.001% nano MoBe 12 , the remainder is Cu.

[0009] Furthermore, nano NbBe 12 or Nano MoBe 12The particle size is 50nm~100nm.

[0010] The high-strength cadmium-free and low-silver silver solder of the present invention uses silver plate, cathode copper, zinc ingot, tin ingot and metal nickel added in proportion and smelted by medium-frequency smelting process. Before casting, copper foil is used to cover trace nano NbBe 12 With MoBe 12 The powder is placed in a graphite "bell jar" and quickly inserted into the molten solder liquid. After stirring evenly, it is cast into an ingot, and then extruded and drawn to obtain the required solder wire.

[0011] The solidus temperature of the solder of the present invention is ≤660°C, and the liquidus temperature is ≤720°C. When the solder is used with the commercially available FB102 solder, the shear strength of the soldered joint is significantly higher than that of the existing BAg12CuZn(Si) solder and BAg5CuZn(Si) solder when soldering red copper-Q235 steel, red copper-brass, and brass-stainless steel.

[0012] The present invention increases the nickel content to 5.0% to 5.5%, and utilizes NbBe with stable chemical properties and high melting point. 12 (melting point 1690℃) and MoBe 12 (melting point is 1705℃) as the "nucleation point" of low-silver silver solder and the "modifier" of Cu6Sn5, so that when the Sn addition in the low-silver silver solder is as high as 14.5% to 15.5%, it can still be smoothly processed into wire, and the melting temperature of the solder is significantly reduced, that is, the solidus temperature is ≤660℃, and the liquidus temperature is ≤720℃. DETAILED DESCRIPTION

[0013] Compared with previous studies, the technical solution of the present invention creatively solves the following key technical problems:

[0014] (1) It was found that adding trace amounts of nano NbBe to high-strength cadmium-free low-silver silver solder with a silver content of 7.5% to 8.5% 12 、MoBe 12 (particle size is 50nm ~ 100nm) can significantly refine Cu6Sn5 grains and significantly inhibit the formation of Cu6Sn5, while greatly increasing the Ni content to 5.0% ~ 5.5%, which can significantly transform the brittle and hard Cu6Sn5 into (Cu, Ni)6Sn5 intermetallic compounds with good plasticity, so that the solder of the present invention can still be smoothly processed into wire even when the Sn content is as high as 14.5% ~ 15.5%.

[0015] Although the document CN 115533366A reports that adding trace rare earth metal Sm, metal Yb elements and trace nano Sm2O3 and nano Yb2O3 oxides to high tin copper-phosphorus solder can significantly refine the grains of copper-phosphorus solder, especially the grains of intermetallic compounds Cu6Sn5 and (Cu,Ni)6Sn5, the maximum particle size of the intermetallic compound (i.e. (Cu,Ni)6Sn5) can only reach ≤5μm, and the amount of Sn added to the solder can only reach 8.0% to 11.0%. However, the present invention adopts the method of adding trace nano NbBe 12 、MoBe 12 The technical solution can refine the maximum particle size of the intermetallic compounds Cu6Sn5 and (Cu,Ni)6Sn5 to ≤2.5μm, so that the solder of the present invention can be smoothly processed into wire even when the Sn content is as high as 14.5% to 15.5%, which is not achieved by the prior art and has not been reported. In addition, the addition of 14.5% to 15.5% Sn content also makes the melting temperature range of the high-strength cadmium-free and low-silver silver solder of the present invention significantly lower than the solidus line of 820°C and the liquidus line of 870°C of the BAg5CuZn(Si) solder to the solidus line ≤660°C and the liquidus line ≤720°C, which fully meets the brazing requirements of copper-containing and copper alloy structures.

[0016] (2) It was found that adding Ni to 5.0% to 5.5% can significantly transform the brittle and hard Cu6Sn5 into a (Cu,Ni)6Sn5 intermetallic compound with good plasticity. At the same time, adding trace amounts of nano-NbBe 12 、MoBe 12 , using Ni and nano NbBe 12 、Nano MoBe 12 The "synergistic effect" can refine the maximum particle size of Cu6Sn5 and (Cu,Ni)6Sn5 to ≤2.5μm, so that the solder of the present invention can be smoothly processed into wire even when the Sn content is as high as 14.5% to 15.5%. In the present invention, the high-strength cadmium-free and low-silver silver solder not only significantly improves the plasticity of the solder through "fine grain strengthening", but also makes the new solder easy to process, and there is no need to adjust the original equipment and process during extrusion and drawing. In addition, the strength of the solder joints of the new solder is also significantly improved (compared with the BAg5CuZn(Si) solder and BAg12CuZn(Si) solder, the strength of the solder joints is increased by more than 30%), which is not achieved by the prior art and has not been reported.

[0017] The test found that the high-strength cadmium-free low-silver silver solder of the present invention has significantly improved the solder spreading area on copper, H58 brass, Q235 steel and 304 stainless steel, compared with BAg12CuZn(Si) and BAg5CuZn(Si), with an improvement of more than 20%; the tensile strength (σ b ) and shear strength (τ) were increased by more than 30%, far exceeding the levels of BAg12CuZn(Si) and BAg5CuZn(Si) solder brazing joints, see Table 1.

[0018] The nano NbBe of the present invention 12 and Nano MoBe 12 The nano powder can be synthesized by using commercial products or by chemical reduction. The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0019] Example 1

[0020] A high-strength cadmium-free low-silver silver solder, the mass percentage ratio is: 7.5% Ag, 43.5% Zn, 14.5% Sn, 5.5% Ni, 0.0005% nano NbBe 12 , 0.001% nano MoBe 12 , the remainder is Cu.

[0021] The high-strength cadmium-free, low-silver solder obtained by the above composition ratio has a solidus of ≤660℃ and a liquidus of ≤720℃ (both considering the measurement error). It has excellent wetting and spreading properties on copper, H58 brass, Q235 steel, and 304 stainless steel. When using flame brazing with FB102 brazing flux, the brazing seam strength when the brazing base materials are the following combinations is shown in the brackets: copper-H58 brass (σ b =270±10MPa, τ=265±10MPa), copper-Q235 steel (σ b =360±10MPa, τ=360±10MPa), H58 brass-304 stainless steel (σ b =370±10MPa, τ=365±10MPa). The brazing joint strength of the solder is significantly higher than that of the solders BAg12CuZn(Si) and BAg5CuZn(Si) under the same conditions.

[0022] Example 2

[0023] A high-strength cadmium-free low-silver silver solder, the mass percentage ratio is: 8.5% Ag, 38.5% Zn, 15.5% Sn, 5.0% Ni, 0.001% nano NbBe 12 , 0.0005% nano MoBe 12, the remainder is Cu.

[0024] The high-strength cadmium-free, low-silver solder obtained by the above composition ratio has a solidus of ≤660℃ and a liquidus of ≤720℃ (both considering the measurement error). It has excellent wetting and spreading properties on copper, H58 brass, Q235 steel, and 304 stainless steel. When using flame brazing with FB102 brazing flux, the brazing seam strength when the brazing base materials are the following combinations is shown in the brackets: copper-H58 brass (σ b =270±10MPa, τ=265±10MPa), copper-Q235 steel (σ b =360±10MPa, τ=360±10MPa), H58 brass-304 stainless steel (σ b =370±10MPa, τ=365±10MPa). The brazing joint strength of the solder is significantly higher than that of the solders BAg12CuZn(Si) and BAg5CuZn(Si) under the same conditions.

[0025] Example 3

[0026] A high-strength cadmium-free low-silver silver solder, the mass percentage ratio is: 8.0% Ag, 41.5% Zn, 15.0% Sn, 5.25% Ni, 0.0008% nano NbBe 12 , 0.0008% nano MoBe 12 , the remainder is Cu.

[0027] The high-strength cadmium-free, low-silver silver brazing alloy obtained by using the above composition ratio has a solidus of ≤660℃ and a liquidus of ≤720℃ (both considering the measurement error). It has excellent wetting and spreading properties on copper, H58 brass, Q235 steel, and 304 stainless steel. When using flame brazing with FB102 brazing flux, the brazing seam strength when the brazing base materials are the following combinations is shown in the brackets: copper-H58 brass (σ b =270±10MPa, τ=265±10MPa), copper-Q235 steel (σ b =360±10MPa, τ=360±10MPa), H58 brass-304 stainless steel (σ b =370±10MPa, τ=365±10MPa). The brazing joint strength of the solder is significantly higher than that of the solders BAg12CuZn(Si) and BAg5CuZn(Si) under the same conditions.

[0028] Comparative Example 1

[0029] A cadmium-free low-silver silver solder, the mass percentage ratio is: 8.0% Ag, 41.5% Zn, 15.0% Sn, 0.0008% nano NbBe12 , 0.0008% nano MoBe 12 , the remainder is Cu.

[0030] The cadmium-free low-silver solder obtained by the above-mentioned composition ratio has no change in the solidus temperature and liquidus temperature of the solder (such as solidus temperature ≤ 660°C, liquidus temperature ≤ 720°C (both considering the measurement error)), but the processing performance is significantly reduced. The wetting and spreading performance on copper, H58 brass, Q235 steel, and 304 stainless steel is also significantly worse than that in the embodiment. When using flame brazing with FB102 brazing flux, the brazing seam strength of the following combinations of brazing base materials is reduced. See the data in brackets: copper-H58 brass (σ b =250±10MPa, τ=245±10MPa), copper-Q235 steel (σ b =340±10MPa, τ=335±10MPa), H58 brass-304 stainless steel (σ b =345±10MPa, τ=335±10MPa).

[0031] Although the brazing joint strength of the comparative example 1 solder is higher than the brazing joint strength of the BAg12CuZn(Si) solder and the BAg5CuZn(Si) solder obtained under the same conditions, it is significantly lower than that of Examples 1, 2 and 3.

[0032] Comparative Example 2

[0033] A cadmium-free low-silver silver solder comprises, by mass percentage, 8.0% of Ag, 41.5% of Zn, 15.0% of Sn, 5.25% of Ni, and the balance of Cu.

[0034] The cadmium-free low-silver silver solder obtained by the above composition ratio has a solidus temperature of ≤660℃ and a liquidus temperature of ≤720℃ (both considering the measurement error), but the processing performance is significantly reduced. The wetting and spreading performance on copper, H58 brass, Q235 steel, and 304 stainless steel is also significantly worse than that of the embodiment. When using flame brazing with FB102 brazing flux, the brazing seam strength of the following combinations of brazing base materials is reduced. See the data in brackets: copper-H58 brass (σ b =250±10MPa, τ=245±10MPa), copper-Q235 steel (σ b =340±10MPa, τ=335±10MPa), H58 brass-304 stainless steel (σ b =345±10MPa, τ=335±10MPa).

[0035] Although the brazing joint strength of the comparative example 2 solder is higher than the brazing joint strength of the BAg12CuZn(Si) solder and the BAg5CuZn(Si) solder obtained under the same conditions, it is significantly lower than that of Examples 1, 2 and 3.

[0036] Table 1 shows the solder spreading performance (spreading area, mm2) of Examples 1 to 3 and commercially available BAg5CuZn(Si) solder and commercially available BAg12CuZn(Si) solder. 2 ) and brazing seam strength data. From the data of Comparative Examples 1 and 2, it can be seen that adding metal Ni or nano NbBe alone 12 、MoBe 12 , the wetting and spreading performance of the solder will deteriorate, and the mechanical properties of the solder joint will also decrease significantly, which fully demonstrates that Ni and nano-NbBe 12 、Nano MoBe 12 The "synergistic effect" has a significant impact on the solder spreading performance and brazing seam strength.

[0037] Table 1

[0038]

Claims

1. A high-strength cadmium-free low-silver silver solder, characterized in that: The mass percentage ratio is: 7.5% to 8.5% Ag, 38.5% to 43.5% Zn, 14.5% to 15.5% Sn, 5.0% to 5.5% Ni, 0.0005% to 0.001% nano NbBe 12 , 0.0005%~0.001% nano MoBe 12 , the remainder is Cu.

2. The high-strength cadmium-free low-silver silver solder according to claim 1, characterized in that: Nano NbBe 12 or Nano MoBe 12 The particle size is 50nm~100nm.

Citation Information

Patent Citations

  • High-tin rare earth copper phosphorus brazing filler metal and preparation method thereof

    CN115533366A

  • Brass brazing alloy

    CN102601542A

  • Low-silver cadmium-free silver solder

    CN109894771A

  • Cadmium-free low-silver solder

    CN115533365A

  • Cadmium-free low-silver solder

    CN116871736A